2001
DOI: 10.1081/ese-100104132
|View full text |Cite
|
Sign up to set email alerts
|

The Removal of Bacteria by Modified Natural Zeolites

Abstract: The removal effect of natural and modified zeolites containing different heavy metals (Ni2+, Zn2+, Fe3+ and Cu2+) on pure cultures of Escherichia coli and Staphylococcus aureus in a solid medium was evaluated in this work. These experiments were carried out in a continuous mode treating municipal wastewater. Faecal coliform species and Pseudomonas aeruginosa were identified. The rate constants of heavy metal lixiviation were determined using a first order kinetic model. The removal effect of modified natural z… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 19 publications
1
13
0
Order By: Relevance
“…Under this context, Mila´n et al (2001) used metallic (Ni 2+ , Zn 2+ , Fe 3+ and Cu 2+ ) modified natural zeolites as disinfectant agents in a column system. The best results were obtained when the initial bacterial concentration in the municipal wastewater was 10 6 NVC/100 mL.…”
Section: Introductionmentioning
confidence: 99%
“…Under this context, Mila´n et al (2001) used metallic (Ni 2+ , Zn 2+ , Fe 3+ and Cu 2+ ) modified natural zeolites as disinfectant agents in a column system. The best results were obtained when the initial bacterial concentration in the municipal wastewater was 10 6 NVC/100 mL.…”
Section: Introductionmentioning
confidence: 99%
“…[2] When water disinfection is applied using chlorine, different toxic and carcinogenic by-products are formed. However, ozone utilization is limited because of its cost; and UV requires previous water treatment for solids removal and membrane filters do not last long, having also a high energetic cost.…”
Section: Introductionmentioning
confidence: 99%
“…Disinfection of water can be achieved using chemical and physical agents such as chlorine and its derivatives, ozone or ultraviolet light [1][2][3][4][5][6]. Silver or zinc modified natural zeolites have been proposed as water disinfectants [7][8][9][10]. A study by Rivera-Garza [11] found that a silver modified clinoptilolite-heulandite-rich tuff releases silver ions into water, causing elimination of coliform microorganisms after a 2 h treatment.…”
Section: Introductionmentioning
confidence: 99%